2010
DOI: 10.1007/s10964-010-9569-7
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and School-Based Victimization: Unique Contexts for Adjustment Difficulties During Adolescence

Abstract: Previous research suggests that school-based and electronic victimization have similar negative consequences, yet it is unclear whether these two contexts offer overlapping or unique associations with adolescents' adjustment. 802 ninth-graders (43% male, mean age = 15.84 years), majority being Caucasian (82%), completed measures assessing the prevalence of school and electronic victimization, as well as self-reports on self-esteem, self-efficacy, anxiety, depressive symptoms, and locus of control. Results reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
67
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(86 citation statements)
references
References 29 publications
15
67
1
3
Order By: Relevance
“…This evidence for the concomitant occurrence of cyber victimization with both internalizing and externalizing problems is consistent with previous research, e.g. associating cyberbullying with depression (Didden et al, 2009;Ybarra, 2004), suicide ideation (Turner, Exum, Brame, & Holt, 2013), social anxiety (Fredstrom, Adams, & Gilman, 2011;Juvonen & Gross, 2008), and decreased levels of self-esteem (Didden et al, 2009;Katzer, 2009), as well as detachment, externalized hostility, and delinquency (Patchin & Hinduja, 2006;Sticca, Ruggieri, Alsaker, & Perren, 2013;Topçu, Erdur-Baker, & Capa-Aydin, 2008;Ybarra, 2004). Victims seem to internalize or externalize problems and are less likely to participate in pro-social activities and behaviors.…”
Section: Discussionsupporting
confidence: 90%
“…This evidence for the concomitant occurrence of cyber victimization with both internalizing and externalizing problems is consistent with previous research, e.g. associating cyberbullying with depression (Didden et al, 2009;Ybarra, 2004), suicide ideation (Turner, Exum, Brame, & Holt, 2013), social anxiety (Fredstrom, Adams, & Gilman, 2011;Juvonen & Gross, 2008), and decreased levels of self-esteem (Didden et al, 2009;Katzer, 2009), as well as detachment, externalized hostility, and delinquency (Patchin & Hinduja, 2006;Sticca, Ruggieri, Alsaker, & Perren, 2013;Topçu, Erdur-Baker, & Capa-Aydin, 2008;Ybarra, 2004). Victims seem to internalize or externalize problems and are less likely to participate in pro-social activities and behaviors.…”
Section: Discussionsupporting
confidence: 90%
“…Bullying victimization is a major global public health problem among adolescents that has been linked to a number of behavioral and emotional problems including anxiety (Cohen and Kendall, 2015), depression (Cole et al, 2014;Hamilton et al, 2016), loneliness (Campbell, 2013;Murphy et al, 2015;Storch and Masia-Warner, 2004), social withdrawal (Dill et al, 2004;Runions and Shaw, 2013), low self-esteem (Fredstrom et al, 2011;Jones et al, 2014;Tsaousis, 2016), as well as poor psychosocial adjustment (Nansel et al, 2001). Various meta-analytic studies have also found support for the link between bullying victimization and the onset of depressive symptoms and internalizing problems (Reijntjes et al, 2010;Ttofi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Later research has confirmed this. Victimization is linked to lower self-esteem and self-efficacy and it also results in anxiety, higher stress, depressive symptoms, and locus of control (Fredstorm, Adams, & Gilman, 2011). In the Brown, Demaray, and Secord study (2014) it was found that the relations between cyber victimization and social emotional outcomes differed by gender such that for girls, cyber victimization was related to internalizing problems, depression, and social stress while relations were not found for boys.…”
Section: Cyberbullying and Possible Ways Of Preventionmentioning
confidence: 99%